The protective effects of two varicella vaccination strategies: A Bayesian modeling study in two megacities in South China - Xing Huang; Jialing Li; Yihan Li; Weilin Zeng; Qi Zhu; Jun Liu; Pei Hu; Zhihua Zhu; Zhongyi Fan; Ying Yang; Siqing Zeng; Zhihao Li; et al. (Expert Review of Vaccines)
Background China implemented diverse varicella vaccination strategies from 2012 to 2022, with unclear protective effects. The study aimed to evaluate the effects of two varicella vaccination (VarV) (the two-dose self-paid VarV and the two-dose free VarV) strategies implemented in Guangdong Province, China.Research design and methods We collected data on varicella cases and doses administered to children aged 0–14 in Guangzhou, Shenzhen, and Foshan from 2012 to 2022. Using Bayesian Structured Time Series (BSTS) model, we estimated the effects of the two VarV strategies in Guangzhou and Shenzhen starting from 2018, by referencing Foshan.Results Post-implementation of the two-dose self-paid VarV strategy 36,749 (95% CI: 29070, 44428) and 24,179 (95% CI: 16400, 31958) varicella cases were averted in Guangzhou and Shenzhen, with a protection rate of 41.8% (95% CI: 36.3%, 46.5%) and 38.9% (95% CI: 30.2%, 45.7%), respectively. After the adoption of the two-dose free VarV strategy, a substantial relative protection rate of 64.2% (95% CI: 58.0%, 68.7%) in varicella cases was observed in Shenzhen, with 38,828 (95% CI: 29979, 47677) cases averted by 2022.Conclusions The two-dose VarV strategies have proven highly effective in reducing varicella incidence. The experience in Shenzhen underscores the benefits of a two-dose free VarV strategy.